Evaluation of the Role of Demineralized Freeze-Dried Bone Allograft and Amniotic Membrane in Periodontal Osseous Defects: A Clinical and Radiographic Study - Deepti Chandra; Md Arif Khan; Piyush Gowrav; Rajeev Kumar Jaiswal; Sanjay Gupta; Anu Bhat (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Periodontitis is an inflammatory disease of the supporting tissue leading to progressive destruction of periodontal ligament and alveolar bone, often resulting in furcation defects. Treatment typically involves periodontal flap surgery with osteoplasty and odontoplasty using materials like hydroxyapatite and demineralized freeze-dried bone allograft (DFDBA). This study compares the efficacy of DFDBA alone and combined with amniotic membrane (AM) in the treatment of grade II furcation defects. Materials and Methods: 30 patients with grade II furcation defects in mandibular first molars were randomly divided into two groups: Group A (control) received DFDBA, and Group B (experimental) received DFDBA with AM. Clinical and radiographic parameters, including plaque index (PI), gingival index (GI), vertical probing depths (VPD), clinical attachment level (CAL) and radiographic bone gain, were assessed at baseline, 1, 3, and 6 months. Conclusion: DFDBA, with or without AM, significantly regenerates grade II furcation defects.